2022
DOI: 10.1371/journal.pone.0278456
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mastitis in camel using high-throughput sequencing

Abstract: Camel milk is recognized as a functional food with significant economic value. Mastitis is one of the most common and costly diseases in the dairy industry. Mastitis, which is caused by pathogens such as bacteria, viruses, fungi, and algae, has an impact on the quality and quantity of milk produced as well as animal health and welfare. There is a paucity of data on the etiological factors that cause camel mastitis. This study reports the bacterial and fungal community involved in clinical camel mastitis using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Pang et al [25] found a reduction in the abundance of this genus in a group of cows with mastitis compared with that in healthy cows. Similar findings were observed in a study on the microbiota associated with mastitis in camels [26]. Our results are also consistent with previous data, as we observed a decrease in the abundance of this genus in the clinical mastitis group compared with that in the healthy group.…”
Section: Discussionsupporting
confidence: 93%
“…Pang et al [25] found a reduction in the abundance of this genus in a group of cows with mastitis compared with that in healthy cows. Similar findings were observed in a study on the microbiota associated with mastitis in camels [26]. Our results are also consistent with previous data, as we observed a decrease in the abundance of this genus in the clinical mastitis group compared with that in the healthy group.…”
Section: Discussionsupporting
confidence: 93%
“…Dromedary camels ( Camelus dromedarius ) are resilient, multi-purpose animals well adapted for survival in harsh environments characterised by scarcity of water and pasture (Darwish, 2023; Seligsohn et al, 2020). Camels are a vital source of income, milk and meat for pastoralists in Arid and Semi-Arid Lands (ASALs) of Africa (Guliye et al, 2007; Volpato and Howard, 2014) with camel milk being an important alternative source of protein and a particularly appropriate functional food for infants and geriatrics due to its high nutrients content in these regions (Alhaj and Kanhal, 2010; Rahmeh et al, 2022). Moreover, camel milk has been reported as a potential remedy for jaundice, tuberculosis, diabetes, asthma and leishmaniasis (Swelum et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In arid and semi-arid regions, camels serve as valuable sources of both meat and milk. Additionally, camels have been historically utilized as a means of transportation [ 1 – 3 ]. The milk produced by camels possesses nutritional qualities akin to those of other dairy animals’ milk, encompassing all essential nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, camels continue to produce milk even under stressful circumstances like drought, while other milk-producing animals cease lactation. Camels exhibit an extended duration of lactation, yielding around 5–6 l of milk per day, even during periods of drought [ 1 – 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation